Healthcare access barriers for FARC ex-combatants in Colombia: qualitative perspectives from healthcare providers and FARC health promoters - Christopher W. Reynolds; Leonar G. Aguiar; Christian Arbelaez; Carlos Gómez Restrepo; Andres Patiño; Heidy Carranza; Lindsey Pileika; Andrés Duarte (BMC, 2021)
Abstract Background Following the 2016 Peace Agreement with the Fuerzas Armadas Revolucionarias de Colombia (FARC), Colombia promised to reincorporate more than 13,000 guerrilla fighters into its healthcare system. Despite a subsidized healthcare insurance program and the establishment of 24 Espacios Territoriales de Capacitación y Reincorporación (ETCRs-Territorial Spaces for Training and Reintegration) to facilitate this transition, data has shown that FARC ex-combatants access care at disproportionately lower rates, and face barriers to healthcare services. Methods Semi-structured interviews were conducted with FARC health promoters and healthcare providers working in ETCRs to determine healthcare access barriers for FARC ex-combatants. Analysis was completed with a qualitative team-based coding method and barriers were categorized according to Julio Frenk's Domains of Healthcare Access framework. Results Among 32 participants, 25 were healthcare providers and 7 self-identified as FARC health promoters. The sample was majority female (71.9%) and worked with the FARC for an average of 12 months in hospital, health center, medical brigade, and ETCR settings. Our sample had experiences with FARC across 16 ETCRs in 13 Departments of Colombia. Participants identified a total of 141 healthcare access barriers affecting FARC ex-combatants, which affected healthcare needs, desires, seeking, initiation and continuation. Significant barriers were related to a lack of resources in rural areas, limited knowledge of the Colombian health system, the health insurance program, perceived stigma, and transition process from the FARC health system. Conclusions FARC ex-combatants face significant healthcare access barriers, some of which are unique from other low-resource populations in Colombia. Potential solutions to these barriers included health insurance provider partnerships with health centers close to ETCRs, and training and contracting FARC health promoters to be primary healthcare providers in ETCRs. Future studies are needed to quantify the healthcare barriers affecting FARC ex-combatants, in order to implement targeted interventions to improve healthcare access.